Re-Politicising Merger Policy: Regulating Foreign Takeovers in Britain and Italy - Bernardo Rangoni; Mark Thatcher (London School of Economics and Political Science (LSE), European Institute, 2023)
While much attention has been given to 'de-politicisation', its reversal through 'repoliticisation' is also possible. We examine 'institutional re-politicisation' - increases in the formal powers and discretion of elected politicians' - in hard cases - policies for regulating Cross-Border Mergers and Acquisitions (CBMAs), focusing specifically on Britain and Italy. While existing explanations of increased powers and discretion for elected politicians to block or shape overseas takeovers focus on economic vulnerabilities created by the Covid pandemic and security concerns vis-à-vis China, using process tracing and comparison we show that, in both countries, the change of tide towards re-politicisation actually begun earlier. We find that it followed specific CBMAs in sectors such as chocolate and dairy products that were contested by political parties from the Right and Left and producer interests, who shared arguments about defending national culture and heritage. The cases suggest there is considerable scope for re-politicisation thanks to a wide coalition that shares arguments based on defending national identity.
Keywords: 330